Community empowerment through making variations of nuggets as an effort to improve the family economy during the Covid-19 pandemic - Triwara Buddhisatyarini; Retno Wulandari; Francy Rivansuna Fifintari (Universitas Muhammadiyah Magelang, 2022)
People have found it challenging to meet their household necessities as a result of the restrictions imposed by the Covid-19 epidemic since their income has fallen while their needs have risen. The training on how to make nuggets from a variety of food ingredients for personal use and can be used as an effort to raise family income is the purpose of this community service. The variety of these nuggets will meet the tastes of family members and consumers. This service activity was carried out for members of the Women Farmers Group (KWT) Mina Julantoro, Gedongkiwo Village, Mantrijeron Yogyakarta. Methods in this service activity include counseling, training and mentoring, monitoring and evaluation. The KWT members were incredibly enthused about taking part in the program. The KWT members also prepared nuggets at home using a variety of ingredients after the training. It is intended that the community can use its abilities to create a business that produces this variety of nuggets through home companies that can improve nutrition and family income.